Actinomycetes‐mediated biogenic synthesis of metal and metal oxide nanoparticles: progress and challenges. (1st June 2017) - Manimaran, M.; Kannabiran, K.
Abstract: Actinomycetes‐mediated biogenic synthesis of metal nanoparticles and their antimicrobial activities are well documented. Actinomycetes facilitate both intracellular and extracellular metal nanoparticles synthesis and are efficient candidates for the production of polydispersed, stable and ultra‐small size metal nanoparticles. Secondary metabolites and new chemical entities derived from Actinomycetes have not been extensively studied for the synthesis of metal/metal oxide nanoparticles. The present review focuses on biogenic synthesis of metal nanoparticles from Actinomycetes and the scope for exploring Actinomycetes‐derived compounds (enzymes, organics acids and bioactive compounds) as metal and metal oxide reducing agents for the synthesis of desired nanoparticles. This review also focuses on challenges faced in the applications of nanoparticles and the methods to synthesize biogenic metal nanoparticles with desired physiochemical properties such as ultra‐small size, large surface to mass ratio, high reactivity etc. Methods to evade their toxicity and unique interactions with biological systems to improve their chance as an alternative therapeutic agent in medical and pharmaceutical industry are also discussed.